2009
DOI: 10.1002/chem.200901482
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation of Indigo Molecules in Sepiolite Tunnels

Abstract: Evidence for access of molecules the size of acetone or pyridine to the intracrystalline tunnels of nanofibre clay (sepiolite) has indicated formation of a new type of organic-inorganic nanocomposites. However, the introduction of larger molecules has been a recurring problem. It is now agreed that for indigo, the molecules are located on the external surface and at the ends of the fibres, thus blocking access to internal tunnels. We claim, however, that it is possible for indigo molecules to access the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
93
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(117 citation statements)
references
References 46 publications
22
93
0
2
Order By: Relevance
“…This observation strongly suggests that the folding of the clay is hindered in the presence of indigo. Such a prevention of folding due to the presence of indigo molecules into clay channels for an indigo@sepiolite hybrid 42 was reported by Ovarlez et al To our knowledge, this is the first time that this aspect 13/07/2012 is also shown for palygorskite. The long range structure of the palygorskite clay is thus affected by the presence of indigo, which is in agreement with the presence of the organic dye inside the channels of the clay.…”
Section: Iii2 Indigo@palygorskite Hybridssupporting
confidence: 71%
See 1 more Smart Citation
“…This observation strongly suggests that the folding of the clay is hindered in the presence of indigo. Such a prevention of folding due to the presence of indigo molecules into clay channels for an indigo@sepiolite hybrid 42 was reported by Ovarlez et al To our knowledge, this is the first time that this aspect 13/07/2012 is also shown for palygorskite. The long range structure of the palygorskite clay is thus affected by the presence of indigo, which is in agreement with the presence of the organic dye inside the channels of the clay.…”
Section: Iii2 Indigo@palygorskite Hybridssupporting
confidence: 71%
“…Signet non défini., 31 . Transformation of indigo into an intermediate oxidized form, the dehydroindigo, has also been introduced 32,42 with possible bonding between nitrogen of the organic dye and aluminum site of palygorskite 33 . This study focalizes onto the dehydration/rehydration process and the structural evolution of the palygorskite clay in the absence and the presence of the indigo molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Data are consistent with previous works (Cannings, 1968;Hayashi et al, 1969;Mendelovici, 1973;Nagata et al, 1974;Prost, 1975;Mendelovici and Portillo, 1976;Post, 1978;Myriam et al, 1998;Frost et al, 2001;Jung and Grange, 2004;Ovarlez et al, 2009;Giustetto et al, 2010;Giustetto et al, 2011b;Bukas et al, 2013). Attribution of vibrational modes and related evolution with T rise are summarized in Table 3.…”
Section: Fourier Transform Ir Spectroscopy (Insert Figure 7)supporting
confidence: 91%
“…6) are consistent with previous works (Nagy and Bradley, 1955;Brauner and Preisinger, 1956;Martin Vivaldi and Cano Ruiz, 1956;Caillère and Hénin, 1957;Preisinger, 1959;Hayashi et al, 1969;Nagata et al, 1974;Rautureau and Mifsud, 1977;Ruiz et al, 1996;Weir et al, 2002;Hubbard et al, 2003;Ovarlez et al, 2006Ovarlez et al, , 2009. Although in sepiolite correlations between TGA features and structural changes are not straightforward nor partitioning among different kinds of water so strict (Mifsud et al, 1987), reasonable interpretations can be sketched.…”
Section: Thermogravimetric Analysis (Insert Figure 6)supporting
confidence: 89%
See 1 more Smart Citation